2009
DOI: 10.1016/j.neures.2009.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical evaluation of the protein expression of nerve growth factor and its TrkA receptor in rat limbic regions following electroshock seizures

Abstract: Repeated (but not acute) exposure to brief, noninjurious seizures evoked by minimal electroconvulsive shock (ECS) decreases neuronal death in limbic system and increases mRNA levels for nerve growth factor (NGF). Thus, the induction of NGF is a potential mechanism for the neuroprotection evoked by repeated ECS. The neuroprotective action of NGF is mediated by the TrkA receptor. This study determined whether repeated ECS exposure increased TrkA and NGF protein levels. To determine the functional significance of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 60 publications
3
26
0
Order By: Relevance
“…NGF-ir and TrkA-ir cells in the hypothalamus (including PVN) or hippocampal areas have been detected under physiological conditions in non-stressed adult rodents (Aloe et al, 1990;Badowska-Szalewska et al, 2006a, 2006bConti et al, 2009). Most researchers agree that both NGF and its receptor TrkA are continuously expressed throughout aging and at least the NGF level is unaltered in the hippocampus (Katoh-Semba et al, 1998;Kelly et al, 2000;Williams et al, 2005;Niewiadomska et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…NGF-ir and TrkA-ir cells in the hypothalamus (including PVN) or hippocampal areas have been detected under physiological conditions in non-stressed adult rodents (Aloe et al, 1990;Badowska-Szalewska et al, 2006a, 2006bConti et al, 2009). Most researchers agree that both NGF and its receptor TrkA are continuously expressed throughout aging and at least the NGF level is unaltered in the hippocampus (Katoh-Semba et al, 1998;Kelly et al, 2000;Williams et al, 2005;Niewiadomska et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The same antibodies were used in our previous studies (Badowska-Szalewska et al, 2011a,b). The specificity of the NGF antibody applied here was tested by Western blotting by Conti et al (2009). The specificity of the TrkA antibody was examined by Lee et al (2008).…”
Section: Immunohistochemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…Although there are low levels of nerve growth factor (NGF) and TrkA present in the neocortex (Altar et al, 1991;Merlio et al, 1992), the other neurotrophins and their receptors are more widely expressed throughout the neocortex (Klein et al, 1990;Merlio et al, 1992;Altar et al, 1994). However, the parahippocampal region shows higher levels of neurotrophins compared to rest of the neocortex: NGF (Lin et al, 1996;Conti et al, 2009), brain-derived neurotrophic factor (BDNF, Sato et al, 1996;Vezzani et al, 1999;Engler-Chiurazzi et al, in press), NT-3 (Eagleson et al, 2001) and all three Trk receptors (Bengzon et al, 1993) have been shown to be strongly expressed in the perirhinal cortex. It must be noted that so far, no study has looked at NT-4/5 expression in the perirhinal cortex.…”
Section: Neurotransmission In the Perirhinal Cortexmentioning
confidence: 99%
“…While localization and function of GDNF receptors were potently documented, only few studies reported existence of Trk mRNAs in the nigrostriatal regions [31,52]. Although TrkA-containing cholinergic neurons were distributed in the cerebral cortex and basal forebrain regions [10,17,27], the previous studies denied positive localization of TrkA protein in nigral neurons [6,30,40]. On the other hand, apparently, distribution patterns and dynamic changes of TrkB and TrkC proteins remain obscure in the adult substantia nigra and particularly in Parkinsonian state.…”
Section: Introductionmentioning
confidence: 99%